Review of Sin Dudas (Jamon, 2016) - Rownd, Robert (2016)
Access online through this link: https://www.plarideljournal.org/article/review-sin-dudas-jamon-2016
Keywords: Film reviewing; New People's Army; Extrajudicial executions